A Review on Laser-Induced Graphene-Based Electrocatalysts for the Oxygen Reduction Reaction in Electrochemical Energy Storage and Conversion - Giulia Massaglia; Marzia Quaglio (Nanomaterials, 2025)
The increasing demand for efficient and sustainable energy conversion technologies has driven extensive research into alternative electrocatalysts for the oxygen reduction reaction (ORR). Platinum-based catalysts, while highly efficient, suffer from high costs, scarcity, and long-term instability Laser-Induced Graphene (LIG) has recently attracted considerable interest as an effective metal-free electrocatalyst for oxygen reduction reaction (ORR), owing to its remarkable electrical conductivity, customizable surface functionalities, and multi-scale porous architecture. This review explores the synthesis strategies, physicochemical properties, and ORR catalytic performance of LIG. Additionally, this review offered a detailed overview regarding the effective pole of heteroatom doping (N, S, P, B) and functionalization techniques to enhance catalytic activity. Finally, we highlight the current challenges and future perspectives of LIG-based ORR catalysts for fuel cells and other electrochemical energy applications. Furthermore, laser-induced-graphene (LIG) has emerged as a highly attractive candidate for electrochemical energy conversion systems, due to its large specific surface area, tunable porosity, excellent electrical conductivity, and cost-effective fabrication process. This review discusses recent advancements in LIG synthesis, its structural and electrochemical properties, and its applications in supercapacitors, batteries, fuel cells, and electrocatalysis. Despite its advantages, challenges such as mechanical stability, electrochemical degradation, and large-scale production remain key areas for improvement. Additionally, this review explores future perspectives on optimizing LIG for next-generation energy storage and conversion technologies.